Bilateral Clavicle Fractures with Multiple Rib Fractures and Hemothorax: A Case Report - Nefihancoro, Udi Heru; Kurniawan, Arie (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2026)
Bilateral clavicle fractures are rare and when it occurs, these are generally associated with high-energy trauma which may also associated with thoracic injury. We report a case of a 46-year-old man presenting with bilateral fractures of the clavicle associated with multiple rib fractures and hemothorax after he suffered a road traffic accident, hit by a car from behind and fell with his chest hitting the road. The left clavicle was fixed with a hook plate, the left clavicle was fixed by a S-shaped locking plate. For the thoracic injury, the hemothorax was managed by water seal drainage (WSD) placed on the left lung and the multiple rib fractures was fixed with elective open reduction and internal fixation.